Analysis of left ventricular rotational deformation by 2D speckle tracking echocardiography: a feasibility study in athletes - Hofrichter, Phillipp (Int J Cardiovasc Imaging, 2021)
2D speckle tracking echocardiography (2DSTE) is established to analyse left ventricular (LV) longitudinal function. The analysis of LV rotational deformation is challenging and requires standardization of image acquisition as well as postprocessing analysis. The aim of this study was to test the feasibility to analyse LV rotational deformation using 2DSTE by introducing a novel algorithm for the detection of artefacts. The study was performed in 20 healthy subjects serving as a control group and in 53 competitive sportsmen. Circumferential, radial strain (CS, RS) and LV rotation were analysed by 2DSTE in parasternal short axis views. The stepwise algorithm to exclude potential artefacts starts with the visual estimation of the image quality with respect to complete visualization of all myocardial segments during the entire cardiac cycle followed by the exclusion of data sets in participants with conduction abnormalities. The next step is the optimization of tracking areas and a cross-check of implausible strain waveforms in multiple acquired comparable cineloops. The last step is the exclusion of strain curves with persisting implausible waveforms if standardization failures and incorrect LV wall tracking are fixed. Plausible physiological strain curves were observed in 89% (n = 65/73) of all subjects. In controls all implausible waveforms could be verified as artefacts. The algorithm was applied in 53 professional athletes to test and confirm its feasibility. Abnormal CS waveforms were documented in 25 athletes, verified as artefacts due to tracking failures in 22 athletes and due to incorrect image acquisition in 3 athletes. CS artefacts were mostly located in the basal posterior and lateral LV segments. (endocardial: 6%, n = 4/70; p < 0.05) and basal posterior (endocardial: 8%, n = 5/70; p < 0.05) segments were highly susceptible to artefacts. 2DSTE of parasternal short axis views to analyse circumferential and radial deformation as well as LV rotation is feasible in athletes. The proposed algorithm helps to avoid artefacts and might contribute to standardization of this technique. 2DSTE might provide an interesting diagnostic tool for the detection of viral myocarditis, e.g. in athletes. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10554-021-02213-3.